Simulation: A Gateway From Unknown To Known - Qamruz Zaman; Mussarat Anwar; Sobia Ali; Muhammad Atif; Shahid Iqbal, (Dialogue Social Science Review (DSSR), 2025)
This is an era of globalization and the world is considered as a global village, due to availability of advanced communication networks. Sharing knowledge and information becomes easier and important to make some smart decisions relating to everyday life. In doing so discovery of new knowledge and improvement in the existing one is need of the day. For the said purpose research work gains so much importance and becomes vital for the growth of knowledge and self esteem. It enables us to discover more and more facts so that one may spend an easier and comfortable life and may withstand the challenges of the century. But there are certain phenomenon especially in the fields of medicines and engineering which cannot be try out to set up experiments on it, due to nature of complexity or high risk involve in it. So different types of computer simulations and physical simulators, which replicate the real state of life, may be used to scrutinize the phenomena under alternate conditions. Some of the applications of simulation technique in various fields of life and types of simulations are discussed in this paper. Simulation is the reproduction of the real state of nature through simulators or representation of that state through mathematical models and examine the complex phenomena under alternative situations. There are lots of advantages of simulation technique such as it can provide accurate results in most of the situations and can minimize the risk of experimentation.But despite of all these advantages the use of these procedures proved to be very costly over the real state experimentation.